Labour market policy and environmental fiscal devaluation: a cure for Spain in the aftermath of the Great Recession? - Österreichisches Institut für Wirtschaftsforschung, Vienna; Kratena, Kurt (Vienna, 2014)
"This paper evaluates different options of labour market policy and tax reform with payroll tax reductions for the Spanish economy in the current situation of high unemployment and debt constraints for public and private households. The Spanish economy in the aftermath of the Great Recession is characterised by household debt de-leveraging, continuous public spending cuts and stagnation in output and employment. A disaggregated dynamic New Keynesian (DYNK) model covering 59 industries and five income groups of households is used to evaluate the macroeconomic and labour market impact of the following policy options: 1. subsidising "green jobs" and reduction of hours worked as an active labour market policy measure, 2. environmental fiscal devaluation (reductions in social security contributions balanced by an environmental consumption tax). The results show a significant output and employment multiplier effect of these policies, given the public budget constraint."